Integration of Artificial Intelligence Technology in Indonesian Language Teaching: Innovative Solutions in the Digital Era - Arifah, Irma; Dwi Kuncorowati; Suprapti; Narimo (Journal of Practice Learning and Educational Development, 2025)
The digital era presents significant opportunities for transforming Indonesian language teaching through Artificial Intelligence (AI) technology. This technology offers innovative approaches, including adaptive learning, automated data analysis, and real-time evaluation. This study aims to explore the integration of AI in Indonesian language instruction at the high school level to enhance students' literacy skills. Using a qualitative descriptive method based on literature analysis, the results indicate that AI applications such as educational chatbots and text analysis platforms can improve student engagement and teaching efficiency. However, infrastructure limitations and teacher training remain primary challenges. This article provides recommendations for optimizing AI integration in Indonesian language learning.